PENGARUH KOMITMEN KERJA, STRES KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN BAGIAN SPINNING III PT. APAC INTI CORPORA - Muchammad Ali Huson; Rodhiyah Rodhiyah; Reni Shinta Dewi (Jurnal Ilmu Administrasi Bisnis, 2015)
The need for human resources are not small and labor requirements vary with the complex challenges of the work is a problem for a company. PT. APAC INTI CORPORA engaged in textiles that need to maintain human resources work in order to meet the quantity and quality of the product. However, in 2013 the production and performance of any inconsistency unfavorable assessments on the performance of the employee.The purpose of research to determine the effect of work commitment, job stress, and work discipline on employee performance Spinning Part III PT. APAC INTI CORPORA. This research method is explanatory, data collection through interviews with questionnaires. Proportionate stratified random sampling technique is used with a sample of 87 people. The analysis technique used was qualitative and quantitative. Quantitative analysis using validity, reliability test, correlation coefficient, simple and multiple regression analysis, the coefficient of determination, cross tabulation, and tests of significance.Categorization work commitment is high, but there are some that in the low category. Employee stress is low, but there is still residing in the high category. Discipline employees in good condition, although there is still a lack of good condition. The level of employee performance is good, but there are still employees who have low performance. Results and discussion showed the higher commitment to work, the higher the performance of employees, reduced work stress, the higher the performance of employees, and the better labour discipline, the higher the performance of employees, simultaneously work commitment, work stress, and labour discipline affect employee performance.Companies must increase loyalty to employees, to put forward a conducive atmosphere in work activities, and socializing with good rules, provide counseling regarding the standards and efficiency of work, and the need for further research by the company or outside parties on other variables such motivation, job satisfaction, training work, which can affect employee performance improvement.